Biopori Kompos: Inovasi Hijau Pengelolaan Sampah Organik Berbasis Pemberdayaan Masyarakat - Estyaningtyas, Nandita Rahma; Mayariah, Alya; Ramadana, Muhamad Izra; Nirmala, Dinda Ayu; Rahmawati, Noor Indah (Universitas Muria Kudus, 2025)
The management of organic waste remains a serious challenge in many regions, particularly in residential and rural areas. One innovative solution that can be applied is the use of biopore absorption holes as a natural composting medium. This article discusses the implementation of biopore composting through a participatory approach based on community empowerment. The implementation methods include socialization, technical training, the construction of biopore holes, and monitoring community participation in utilizing household organic waste. The results of the activity indicate an increase in public awareness of waste management, a reduction in the volume of organic waste disposed of, and the production of compost fertilizer that can be used for environmental greening. These findings demonstrate that biopore composting not only serves as an environmentally friendly appropriate technology but also as a means of ecological education and community participation strengthening. Therefore, the implementation of biopore composting has strong potential to be widely replicated as a sustainable organic waste management strategy. Pengelolaan sampah organik masih menjadi tantangan serius di berbagai daerah, terutama di lingkungan perumahan dan pedesaan. Salah satu solusi inovatif yang dapat diterapkan adalah penggunaan lubang resapan biopori sebagai media pengomposan alami. Artikel ini membahas penerapan biopori kompos dengan pendekatan partisipatif berbasis pemberdayaan masyarakat. Metode pelaksanaannya meliputi sosialisasi, pelatihan teknis, pembuatan lubang biopori, hingga monitoring partisipasi warga dalam pemanfaatan sampah organik rumah tangga. Hasil kegiatan menunjukkan peningkatan kesadaran masyarakat terhadap pengelolaan sampah, berkurangnya volume sampah organik yang dibuang, serta terciptanya pupuk kompos yang dapat dimanfaatkan untuk penghijauan lingkungan. Temuan ini membuktikan bahwa biopori kompos bukan hanya berfungsi sebagai teknologi tepat guna ramah lingkungan, tetapi juga sebagai sarana edukasi ekologis dan penguatan partisipasi komunitas. Dengan demikian, penerapan biopori kompos memiliki potensi untuk direplikasi secara luas sebagai strategi pengelolaan sampah organik yang berkelanjutan.